Evaluating a cross-lagged panel model between problematic internet use and psychological distress and cross-level mediation of school administrator support on problematic internet use: The serial mediating role of psychological needs thwarting of online teaching and psychological distress - Chen, I-Hua; Chen, Hsin-Pao; Gamble, Jeffrey H.; Liao, Xiao ling; Chen, Xiu-Mei; Yang, Ya-Ting Carolyn; Pakpour, Amir H.; Griffiths, Mark D.; Lin, Chung-Ying (Frontiers in Public Health, 2022)
Background To reduce the transmission of COVID-19, many teachers across the globe, including teachers in China, were required to teach online. This shift to online teaching can easily result in psychological need thwarting (PNT) of teachers' psychological basic needs (autonomy, competence, and relatedness), leaving them vulnerable to negative psychological outcomes. Resulting negative emotional state may lead to problematic internet use (PIU), which can lead to further psychological distress, forming a vicious cycle. Methods The present study was conducted using a cross-lagged panel model (with longitudinal data) and hierarchical linear modeling (HLM) (with cross-sectional data). The aims were to investigate (i) the reciprocal relationships between two specific forms of PIU [problematic social media use (PSMU) and problematic gaming (PG)] and psychological distress among schoolteachers, and (ii) the influence of administrators' support on schoolteachers' PIU through a cross-level serial mediation model (PNT of online teaching was the first mediator and psychological distress was the second mediator affected by PNT of online teaching). Primary and secondary schoolteachers (N = 980; mean age = 34.76; 82.90% females) participated in two surveys (Time 1: mid-November 2021; Time 2: early-January 2022). Results Results indicated that (i) high psychological distress at Time 1 was associated with increased levels of PSMU and PG at Time 2. Inversely, PG at Time 1 was associated with increased psychological distress at Time 2, although PSMU at Time 1 did not have a significant influence on psychological distress at Time 2; (ii) during Time 1, increased administrative support contributed to alleviating teachers' psychological needs thwarting of online teaching, thereby lowering their psychological distress which, in turn, resulted in a decrease in PG. Conclusion PG had a stronger negative influence on teachers' psychological distress than PSMU. To relieve teachers' PG, administrative support can alleviate teachers' psychological needs thwarting of online teaching and psychological distress. Based on this finding, school managers must consider effective ways to support teachers during mandatory online teaching.